2019
DOI: 10.37358/rc.19.8.7468
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Liaison Between Diabetes and Hypertension, Depression and Socio-economic Deprivation Impact in Both

Abstract: Approaching two prevalent chronic conditions as Diabetes mellitus (DM) and High blood pressure/Hypertension (HTN) from a socio-economic and mental health perspectives using Beck Depresion Inventory (BDI) and EPICES score simultaneouslyis a first for Arad County and for Romania. This research demonstrates the connection between the disease and the socio-economic pressures that lead to deprivation and depression and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The best indicator of vitamin D status in the body is considered to be serum 25-hydroxyvitamin D, 25-[OH]D [1][2]. This is known to be the renal and nonrenal synthesis precursor for 1,25dihydroxyvitamin D, 1,25-[OH]2D (calcitriol) which, opposed to the previous, has a greater biological half-life of three weeks and higher circulating levels [3][4][5][6][7]. Serum 1,2D is the biologically active form of vitamin D that is responsible for most of the vitamin D actions and it does not cross the placenta [2].…”
Section: Metabolism Of Vitamin D During the Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The best indicator of vitamin D status in the body is considered to be serum 25-hydroxyvitamin D, 25-[OH]D [1][2]. This is known to be the renal and nonrenal synthesis precursor for 1,25dihydroxyvitamin D, 1,25-[OH]2D (calcitriol) which, opposed to the previous, has a greater biological half-life of three weeks and higher circulating levels [3][4][5][6][7]. Serum 1,2D is the biologically active form of vitamin D that is responsible for most of the vitamin D actions and it does not cross the placenta [2].…”
Section: Metabolism Of Vitamin D During the Pregnancymentioning
confidence: 99%
“…Its action is focused on the three target organs, intestine, kidney, and bone, in which specific nuclear receptors (VDRs) are well expressed [3]. The studies and experiments conducted in vitro and in vivo have shown that vitamin D exerts other "non-calcium" actions also [1][2][3][4][5][6]. It was demonstrated that vitamin D receptors are located in the entire body tissues [1].…”
Section: Introductionmentioning
confidence: 99%
“…Because the patient initially refused surgery, treatment with pasireotide was initiated at a dose of 0.6 mg twice daily. After 18 months she experienced spectacular weight loss of 32 kg, her blood pressure normalized, requi- a higher frequency of hyperglycemia 2,[6][7][8] . In a metaanalysis, mild side eff ects were observed in 39.3% of patients and severe side eff ects were observed in 15.2% of patients, respectively 1 .…”
Section: Case Presentationmentioning
confidence: 99%